Marfan syndrome diagnosis and management - Ammash, Naser M.; Connolly, Heidi M. (SA Heart Journal, 2017)
Marfan syndrome is the most common inherited multisystem disorder of connective tissue. This autosomal dominant condition has an incidence of 2-3 per 10,000 individuals. Although genetic diagnostic techniques are available, the diagnosis is primarily made using the Ghent diagnostic criteria. Early identification and appropriate management improves the prognosis of patients with Marfan syndrome who are prone to the life-threatening cardiovascular complications of aortic dissection and rupture. Beta-blockers have been demonstrated to slow aortic growth and thus delay the time to aortic surgery. Operative intervention has markedly changed the prognosis of patients with Marfan syndrome and can be safely performed on an elective basis. The advance in the understanding of the cause of Marfan syndrome, as well as early recognition of the disorder and subsequent institution of medical and surgical therapy has resulted in dramatic improvement.